2000
DOI: 10.1007/s003830050741
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phospholipase A 2 on bacterial translocation in a cell culture model

Abstract: The activity of phospholipase (PL)A2 is elevated in the intestinal epithelia of patients with inflammatory bowel disease (IBD). Recently, we reported that lysophosphatidylcholine (L-PC), the PLA2 hydrolysis product of phosphatidylcholine (PC), stimulates bacterial translocation (BT) in an enterocyte cell-culture model. These two observations stimulated us to examine the effects of extracellular PLA2 on intestinal epithelial permeability. Human Caco-2 enterocytes were grown to confluence on porous filters in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…PLC and PKC have both been implicated in the reversible melittin response, with PLA2 and cyclooxygenase-2 inhibitors only having effects after extended periods of time (>3 h). PLA2 activation has been shown to indirectly decrease TER of Caco-2 monolayers (41). While further studies are needed to elucidate a mechanism, it is likely that these prostaglandins play some role in the melittin effects on tight junctions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PLC and PKC have both been implicated in the reversible melittin response, with PLA2 and cyclooxygenase-2 inhibitors only having effects after extended periods of time (>3 h). PLA2 activation has been shown to indirectly decrease TER of Caco-2 monolayers (41). While further studies are needed to elucidate a mechanism, it is likely that these prostaglandins play some role in the melittin effects on tight junctions.…”
Section: Discussionmentioning
confidence: 98%
“…It has been previously been shown that melittin is an activator of PLA2, (40) which resulted in an increase in electrogenic chloride secretion across rat colonic epithelium (24). Activation of PLA2 has been shown to decrease TER of Caco-2 cells via hydrolysis of phosphatidylcholine (41). A number of inhibitors of reported melittin activities were screened to assess the mechanism of action of the peptide on tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of melittin (0.17-0.7 mM) increased Isc due to the peptide_s PLA2 activation, with resultant prostaglandin E2 production. PLA2 is also linked with absorption enhancement, its activation mediates the hydrolysis of phosphatidylcholine to lysophosphatidylcholine which decreased TER in Caco-2 monolayers (35), suggesting that the concurrent permeation enhancing and ion secretory effects of melittin may involve PLA2. Quinacrine, an inhibitor of PLA2, had little effect on apical melittin-induced alterations in barrier function or Isc, suggesting a limited role for PLA2.…”
Section: Discussionmentioning
confidence: 98%
“…These include signalling molecules such as protein kinase C (PKC) (37), phospholipase A2 (PLA2) (35) and calcium dependant calmodulin (38). These aspects of melittin_s activity and its ability to disrupt the integrity of the cell membrane may be involved in the peptide_s cytotoxicity which is considered a limiting factor in the use of melittin in infectious disease (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation